Enhancing effective online teaching in Higher Education - Mustafoeva Noila Ishnazarovna (Zien Journals, 2022)
Over the past twenty years, the use of online education and the inclusion of its individual elements in the educational process, such as electronic or online courses, has increasingly become the subject of research. Thw following article is devoted to the investigation of the ways of enhancing the efficiency of online classes in higher education
Keywords: digital tools; online learning; synchronous; asynchronous